Design of evaluation procedures for letter-based techniques in text ste ganography method - Utama, Sunariya (2017)
Steganography is one of information hiding area that covers the information in any medium domain such as text, image, audio and video. One of steganography categories in the medium of text is called text steganography. It conceals hidden message with embedding the text via various methods such as horizontally shifting, vertically shifting or based on the letter of text structures. Many researchers utilize the feature-based technique to cover hidden message based on uniqueness of letter. Therefore, this study intends to focus on specific type of feature-based technique which is the letter-based text steganography. However, there is still issue relating to this method which the existence of the technique in the text is easily discoverable by attackers. Literature indicated that this issue is probably rooted from the lack of verification and validation procedures during the development of the steganography method. This study aims to identify the suitable parameters for verification and validation process. In addition, the parameters will then be used in conducting evaluation on the letter-based text steganography. The outcome of this study showed that the parameters which involved in verification and validation process will be able to improve the performance and security of the technique.